The Effectiveness of Giving Papaya Fruit (Carica Papaya) Toward Blood Pressure on Elderly Hypertension Patients at the Posyandu Purna Sejahtera Surabaya - Wahdi, Achmad; Astuti, Puji (PROCEEDING SURABAYA INTERNATIONAL HEALTH CONFERENCE 2019, 2020)
Hypertension in elderly happened due to the decrease elasticity of arteries at the process of aging. Based on previous research, papaya is known as complementary therapy to decrease blood pressure in adult patient. The design of this research is Quasi Experiment. The population were 34 elderly people with hypertension at Posyandu Purna Sejahtera Surabaya. There were 34 respondents as sample. Samples were taken by total sampling, which divide into two groups, each group consist of 17 respondents. Research instrument were sphygmomanometer needle, stethoscope and SOP of giving papaya. The data analysis using the Mann Whitney and the Wilcoxon Signed Rank Test Result of this study before intervention to 17 respondents was almost half of respondents (47,1%) had mild hypertension, while after intervention there only small part (35,3%) had normal hypertension. In the first measurement of control group the result obtained that half of respondents (52,9%) also had mild hypertension. Whereas the second measurement was found that almost half of respondents (47,1%) had mild hypertension. The result of Mann Whitney Test was ρ=0,025<α=0,05 then Ho rejected, that means giving papaya has effectiveness to decrease blood pressure at Posyandu Lansia Purna Sejahtera Surabaya.